Growth Response of Teak (Tectona grandis L.f.) Seedlings to Nitrogen, Phosphorus and Potassium Fertilizers - Abod, Sheikh Ali; Siddiqui, Muhammad Tahir (Universiti Putra Malaysia Press, 2002)
Teak (fectona grandis L.f) is one of the high quality timber species in the world. A greenhouse experiment was conducted to determine the growth response of teak seedlings to N, P, K fertilizers. The results of the present study indicated that root weight, leaf area and total plant weight of the teak seedlings were significantly affected by all the three main factors i.e. N, P and K Height increment, leaf weight, shoot weight and root length showed statistically significant responses to N and P fertilizers. The main effects of N and K but not of P were statistically significant for diameter increment. There was significant main effect of N only far root-shoot ratio. The present study also revealed that the application of 564 kg/ha ammonium sulphate, 300 kg/ha triple superphosphate and 75 kg/ha muriate ofpotash are required to enhance height and diameter growth and total plant weight of teak seedlings at nursery stage.